Method for electrically producing hydrated electrons by amphoteric metal cathode and application of hydrated electrons in degradation of perfluorooctanoic acid

Hydrated electrons (eaq-) are generated by amphoteric metal cathode electrolysis and PFOA degradation is performed in a local alkaline environment, which solves the problem of difficulty in removing PFOA and achieves efficient and sustainable degradation effects.

CN119683741AActive Publication Date: 2025-03-25WUXI CITY COLLEGE OF VOCATIONAL TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411849627.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Perfluorooctanoic acid (PFOA) is difficult to remove efficiently due to its high structural stability and resistance to traditional degradation technologies. The prior art has problems such as high operating costs, high separation complexity and insufficient efficiency.

Method used

Hydrated electrons (eaq-) are generated by amphoteric metal cathode electrolysis, eaq- is generated in a local alkaline environment, and is used to perform efficient electroreduction and degradation of PFOA.

Benefits of technology

The efficient degradation and defluorescence of PFOA is achieved, reducing operating costs and separation complexity, and the method is feasible and more sustainable without the need for a large amount of energy input and additional chemical reagents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683741A_ABST
    Figure CN119683741A_ABST
Patent Text Reader

Abstract

The invention discloses a method for electrically producing hydration electrons by using an amphoteric metal cathode and application of the method in degradation of perfluorooctanoic acid, and belongs to the technical field of electrochemical wastewater treatment. The invention firstly shows that the amphoteric metal is used as the cathode of the diaphragm electrolytic cell for electrolysis to generate eaq <->, and the efficient electroreduction of PFOA and other fluorine-containing organic matters is realized under the local alkaline condition, which is also the first attempt to produce eaq <-> under the environmental conditions of not needing a large amount of energy input and additionally adding chemical reagents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical wastewater treatment, and specifically relates to a method for electrogenerating hydrated electrons using an amphoteric metal cathode and an application thereof in degrading perfluorooctanoic acid. Background Art

[0002] Perfluorooctanoic acid (PFOA) is a class of compounds containing CF bonds, formed by fluorine atoms replacing some or all of the hydrogen atoms on carbon atoms. Since its synthesis in the 1940s, PFOA has been widely used in textiles, food packaging, firefighting foams, protective coatings and related industrial fields due to its high heat resistance, chemical stability, hydrophobicity and oleophobicity. PFOA is known for its neurotoxicity, genetic and reproductive toxicity, and potential carcinogenicity. In recent years, PFOA has been frequently detected from industrial wastewater, groundwater and surface water. Therefore, it is crucial to develop efficient technologies for removing PFOA from water.

[0003] However, due to the strong electronegativity of fluorine and the high structural stability of the carbon-fluorine bond (bond energy of 485.3 kJ·mol -1 ), the degradation of PFOA is still a technical difficulty. PFOA is resistant to biodegradation, chemical oxidation and even ·OH (k = 2.6 × 10 5 M-1·s -1 ) and SO4 ·- (2.59×10 5 M -1 ·s -1 ) are highly resistant to advanced oxidation processes. From a thermodynamic point of view, reduction reactions may be more favorable than oxidation reactions to cleave PFOA, and theoretically a potential of at least +2.2V (relative to the standard hydrogen electrode, SHE) is required to induce dissociative electron transfer (DET) of the CF bond by oxidation, while only -1.1V vs SHE is required to trigger the reduction of PFAS. The most commonly used PFAS reduction methods include zero-valent iron (ZVI), photocatalysis, electrochemistry, and hydrated electron (e-based) reduction. aq - ) Advanced Restore Procedures (ARPs). aq - Considered to be the strongest reducing agent (E θ = -2.87 V vs SHE), capable of reacting non-selectively with most compounds under thermodynamically feasible and kinetically fast conditions (10 6 -10 10 L·mol -1 ·s -1 ). In addition, e aq - It has a high nucleophilicity, which enables it to subsequently react with halogen atoms involved in organic molecules.aq - Advanced reduction technology for the efficient removal of PFOA has attracted the attention of many researchers.

[0004] So far, e aq - Mainly through UV excitation photosensitizer (such as I - and SO3 2- ), produced by electron beam / gamma ray irradiation of water and alkali metals dissolved in liquid ammonia solution. For environmental applications, e aq - It is a simple strategy. aq - The yield is relatively high, but due to (i) secondary contamination caused by the addition of sulfite, (ii) aq - The high pH dependence of the generated products (pH>9.2), as well as (iii) the light shielding effect caused by coexisting anions and natural organic matter, make this technology challenging for environmental applications. Therefore, it is urgent to develop more tractable, general, and efficient strategies to obtain e-waste for PFOA reduction. aq - . Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for electrogenerating hydrated electrons using an amphoteric metal cathode and its application in the degradation of perfluorooctanoic acid.

[0006] Basically, e aq - H2 can be produced through a fast dimerization reaction with a second-order rate constant as high as k = 1.1×10 10 M -1 ·s -1 (Equation 1). If there exists a aq - The dimerization reaction occurs via hydrogen evolution (Eq. 1) rather than the conventional proton exchange (M+H + →M + +H2) and water decomposition (H2O→H2+O2), then according to this reaction equation, develop e aq - Alternative methods of generation are possible. According to classical chemical principles, amphoteric metals can be generated by H-independent + replacement reaction, but with OH - The reaction generates H2 (Equation 2, taking Al as an example), e aq -The dissolution process of aluminum produces (Equation 3). Generally speaking, alkaline conditions are obtained by adding alkaline chemicals to obtain alkaline solutions, but in most cases, maintaining strong alkaline conditions in water purification is unlikely to be the best choice. The present invention uses electrolysis to allow the amphoteric metal as the cathode to create a local high alkaline microenvironment nearby, thereby releasing OH - , generating e aq - (Equation 3, taking Al as an example) Electrochemical-chemical tandem electrogeneration can be achieved by generating a local strong alkaline environment through electrochemical Al cathode electrolysis and inducing Al dissolution in situ. aq - process and realize e aq - Mediated reduction and removal of PFOA.

[0007] e aq - +e aq - →H2+OH - (1)

[0008] Al+OH-→Al(OH)4 - +H2 (2)

[0009] Al+4OH - →Al(OH)4 - +3e aq - (3)

[0010] To achieve the above object, the present invention provides the following technical solutions:

[0011] One of the technical solutions of the present invention is to provide a method for electrogenerating hydrated electrons using an amphoteric metal cathode, comprising the following steps:

[0012] A diaphragm electrolyzer is constructed using amphoteric metals as cathode materials, and hydrated electrons can be generated in the cathode chamber when electricity is applied.

[0013] After the diaphragm electrolyzer constructed by the present invention is energized, a local alkaline environment is formed around the amphoteric cathode, and the locally high concentration of OH is generated. - Reacts with amphoteric metals to produce aq - Taking aluminum as an example, OH - It reacts with aluminum to form tetrahydroxyaluminate ion [Al(OH)4 - ] and e aq - .

[0014] Preferably, the amphoteric metal is aluminum.

[0015] The diaphragm used in the diaphragm electrolyzer constructed by the present invention can be a proton exchange membrane, the anode can be a platinum electrode, and the electrolyte in the electrolyte can be Na2SO4.

[0016] The second technical solution of the present invention is to provide an application of the above-mentioned method of electrogenerating hydrated electrons using an amphoteric metal cathode in the degradation of perfluorooctanoic acid.

[0017] The third technical solution of the present invention is to provide an application of the above-mentioned method of electrogenerating hydrated electrons using an amphoteric metal cathode in the degradation of fluorine-containing organic matter.

[0018] The fourth technical solution of the present invention is to provide a method for degradation of perfluorooctanoic acid mediated by electrogenerated hydrated electrons at an amphoteric metal cathode, comprising the following steps:

[0019] A diaphragm electrolytic cell is constructed using amphoteric metal as the cathode material and an electrolyte containing at least perfluorooctanoic acid as the cathode chamber electrolyte, and the degradation of perfluorooctanoic acid can be achieved by turning on power.

[0020] Preferably, the amphoteric metal is aluminum.

[0021] The fifth technical solution of the present invention is to provide a method for degradation of fluorine-containing organic matter mediated by electrogenerated hydrated electrons at an amphoteric metal cathode, comprising the following steps:

[0022] Amphoteric metals are used as cathode materials, and an electrolyte containing at least fluorinated organic matter is used as the cathode chamber electrolyte to construct a diaphragm electrolytic cell, and the degradation of fluorinated organic matter can be achieved by powering on.

[0023] Preferably, the amphoteric metal is aluminum.

[0024] The beneficial technical effects of the present invention are as follows:

[0025] e aq - As one of the most active reducing species, it has broad application prospects in the reduction and decomposition of difficult-to-degrade PFOA water treatment. aq - It is usually obtained by ultraviolet light excitation of photosensitizers and electron beam / gamma ray irradiation, which increases operating costs, separation complexity and inefficiency. This invention demonstrates for the first time the use of amphoteric metals as cathodes in diaphragm electrolytic cells to produce e aq - The highly efficient electroreduction of PFOA and other fluorinated organic compounds was achieved under local alkaline conditions, which is also the first attempt to produce e-reduction under environmental conditions without requiring large amounts of energy input and the addition of additional chemical reagents. aq - This will make the reductive removal of PFOA more efficient, easier to handle and more sustainable. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 : This is the effect of different current densities on the degradation of PFOA in Example 1, wherein a is the change of PFOA degradation over time, and b is the change of defluorination rate over time.

[0027] Figure 2 The current density is 25 mA·cm in Example 1. -2 Figure 3 SEM images and AFM images of the original aluminum cathode, the aluminum cathode after 1 electrolysis cycle (4h) and 10 electrolysis cycles (40h), where a is the SEM image of the original aluminum cathode, d and g are the AFM images of the original aluminum cathode, b is the SEM image of the aluminum cathode after 1 cycle, e and h are the AFM images of the aluminum cathode after 1 cycle, c is the SEM image of the aluminum cathode after 10 cycles, and f and i are the AFM images of the aluminum cathode after 10 cycles.

[0028] Figure 3 The current density is 25 mA·cm in Example 1. -2 The XPS full spectra of the original aluminum cathode, the aluminum cathode after 1 electrolysis cycle (4h) and 10 electrolysis cycles (40h).

[0029] Figure 4 The current density is 25 mA·cm in Example 1. -2 Al 2p spectra of the original aluminum cathode, the aluminum cathode after 1 electrolysis cycle (4h) and 10 electrolysis cycles (40h).

[0030] Figure 5 The current density is 25 mA·cm in Example 1. -2 XRD patterns of the original aluminum cathode, the aluminum cathode after 1 electrolysis cycle (4 h), and the aluminum cathode after 10 electrolysis cycles (40 h).

[0031] Figure 6 The current density is 25 mA·cm in Example 1. -2 Figure 2 EIS spectra of the original aluminum cathode, the aluminum cathode after 1 electrolysis cycle (4 h), and the aluminum cathode after 10 electrolysis cycles (40 h).

[0032] Figure 7 The LSV curves (a) of the original aluminum cathode at a current density of 25 mA·cm-2 in Example 1, the aluminum cathode after 1 electrolysis cycle (4 h) and 10 electrolysis cycles (40 h), the LSV curves of the original aluminum cathode and the Ti cathode (b), the degradation rate of PFOA by the original aluminum cathode and the Ti cathode (c) and the degradation kinetic fitting curve of PFOA degradation by the original aluminum cathode and the Ti cathode (d).

[0033] Figure 8 This is the inhibition of H* scavenger on the degradation of PFOA by aluminum cathode in the quenching experiment.

[0034] Fig. 9 (a) ESR signal obtained using DMPO as a free radical scavenger, (e) aq - The inhibitory effect of scavengers on the degradation of PFOA in the aluminum cathode system (b), the change of the ECL signal of luminol as a probe over time under different conditions (c) and the theoretically calculated local pH value (d).

[0035] Fig.10 This is the degradation kinetic fitting curve of PFOA degradation by aluminum cathode ARP system under different NaNO3 concentrations in the quenching experiment.

[0036] Fig.11 Figure 3 shows the change in the removal rate of PFOA in the aluminum cathode ARP system over time in 10 consecutive experiments (a), the removal rate of OFX and FLO by the aluminum cathode ARP system (b), the degradation rate of PFOA in the aluminum and zinc cathode reduction system (c) and the defluorination rate of PFOA in the aluminum and zinc cathode reduction system (d).

[0037] Fig.12 Based on Al cathode system, the hydrated electrons e aq - Schematic diagram of the degradation mechanism of PFOA. DETAILED DESCRIPTION

[0038] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0039] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0040] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0042] Example 1

[0043] Laboratory construction of PFOA diaphragm electrolyzer based on Al cathode electrohydration electron degradation:

[0044] The experiment was carried out in an H-type reactor with a DuPont proton exchange membrane (Nafion 117) separating the two compartments and a 50 mM Na2SO4 solution as the supporting electrolyte. A commercial aluminum electrode (30 mm × 40 mm) was immersed in a 50 mL PFOA solution (concentration 5.0 mg·L) in the cathode compartment. -1 ), the anode chamber contained a platinum electrode and 50 mL of Na2SO4 solution. The applied current density was set to 10, 25, and 40 mA cm -2 .

[0045] Subsequent analysis and test methods used:

[0046] The concentrations of PFOA and its related degradation intermediates were analyzed using an ultra-high performance liquid chromatography-triple quadrupole tandem mass spectrometer equipped with an ACQUITY BEH C18 column (2.1 mm × 100 mm, 1.7 μm, Waters). -1 ) is calculated by linear fitting of ln(C0 / C) versus reaction time, assuming that the degradation of PFOA is a pseudo-first-order reaction, where C0 and C are the initial concentration and reaction concentration of PFOA, respectively. The concentration of fluoride ions is determined by ion chromatography, and the calculation formula for the defluorination rate is shown in formula (4):

[0047]

[0048] In formula (4), [F - ] is the concentration of fluoride ions in the system after the reaction, [PFOA]0 is the initial concentration of PFOA, 414 is the molecular mass of PFOA, and 285 is the sum of the atomic masses of all fluorine atoms in PFOA.

[0049] Electron spin resonance (ESR, Bruker A300, Germany) was used to detect the generation of atomic hydrogen (H*). During the electrolysis, a scavenger 5,5-dimethyl-1-pyrroline-N-oxide (DMPO, 50 mmol L -1) into the electrolyte, and then the power was immediately turned off. Subsequently, a capillary was used to carefully sample a point close to the cathode surface for ESR analysis. The ESR measurement parameters were: central field 3510G, scan width 100G, microwave frequency 9.87GHz, modulation frequency 100GHz, and power 18.11mW. The morphology, surface roughness, and metal valence of the electrode before and after use were measured and analyzed by ZEISS Sigma 300 scanning electron microscope (SEM, Germany), Bruker Dimension Icon atomic force microscope (AFM, Germany), Rigaku Miniflex600X-ray diffractometer (XRD, Japan), and Thermo Scientific K-Alpha X-ray photoelectron spectrometer (XPS, USA). The electrochemical performance of the aluminum electrode was characterized by an electrochemical workstation (CHI760E, Chenhua InstrumentsCo., China) in a three-electrode H-cell, and an Ag / AgCl (3M NaCl) reference electrode was placed near the working electrode. The electrochemiluminescence (ECL) signal was recorded on a LK5100 instrument (LK5100, Lanlike Co., China) using luminol as a probe (ECL emission wavelength is approximately 425 nm). aq - With the participation of luminol, the luminol luminescent probe is activated and presents electrochemiluminescence signal.

[0050] Analysis results:

[0051] The effect of different current densities on the degradation of PFOA in Example 1 is shown in Figure 1 , where a is the change of PFOA degradation over time, and b is the change of defluorination rate over time.

[0052] Figure 1 The current density is 40, 25 and 10 mA cm -2 When the degradation rates were 99.1%, 97.4% and 80.9%, the corresponding first-order kinetic constants (k obs ) are 0.0169min respectively -1 、0.0125min -1 and 0.0039min -1 The defluorination rate is calculated according to the concentration of fluoride ions in the cathode chamber at different time periods and formula (4), as follows: Figure 1 As shown in b, the current density is 40, 25 and 10 mA cm -2The defluorination rates were 95.3%, 85.2% and 40.7% respectively when the defluorination rate was 25 mA cm-1. The lower defluorination rate compared with the degradation rate may be attributed to the generated fluorine intermediates. This indicates that the electrochemical reduction system based on aluminum cathode can effectively decompose PFOA, and the high efficiency defluorination rate is responsible for the removal of PFOA by the reduction process triggered by electrons. Considering the PFOA removal and energy consumption factors, 25 mA cm-1 was selected. -2 As the optimal current density for subsequent electrolysis tests.

[0053] During the electrolysis process, the morphology of the aluminum cathode was characterized by SEM and AFM (25 mA cm -2 ). The SEM and AFM images of the original aluminum cathode, the aluminum cathode after 1 electrolysis cycle (4h) and 10 electrolysis cycles (40h) are shown in Figure 2 , where a is the SEM image of the original aluminum cathode, d and g are AFM images of the original aluminum cathode, b is the SEM image of the aluminum cathode after 1 cycle, e and h are AFM images of the aluminum cathode after 1 cycle, c is the SEM image of the aluminum cathode after 10 cycles, and f and i are AFM images of the aluminum cathode after 10 cycles.

[0054] like Figure 2 As shown in Figure a, the surface of the original aluminum cathode contains nanoparticles caused by the preparation process (rolling and annealing). After one electrolysis cycle (4 h), the number of nanoparticles decreases compared to its original state, and micropores are formed ( Figure 2 After 10 electrolysis cycles (40 h), significant corrosion occurred on the electrode surface, as evidenced by the formation of more nanoscale pores ( Figure 2 (c). Figure 2 The AFM image of the middle di further illustrates the surface changes before and after use, showing that the surface roughness gradually increases with the continuous electrolysis process. For example, the average roughness of the original electrode surface is 33.0 nanometers, which increases to 49.4 nanometers after 1 cycle and further increases to 109.0 nanometers after 10 cycles. This corrosion phenomenon should be the result of the local enrichment of OH generated on the aluminum electrode. - The result of the reaction.

[0055] In order to evaluate the chemical state of the aluminum electrode during electrolysis, XPS analysis was further performed after SEM and AFM characterization. The full XPS spectrum is shown in Figure 3 , Al 2p spectrum see Figure 4 .

[0056] like Figure 3 As shown in the figure, the spectra of the aluminum electrode before and after use are almost the same, indicating that the aluminum electrode has a uniform composition and high purity. In addition, there is no evidence of new elements generated on the electrode surface, which excludes PFOA or F - Possibility of adsorption on aluminum cathode.

[0057] like Figure 4 As shown in Figure 2, the Al 2p spectrum of the original electrode shows characteristic peaks at 73.48 eV and 75.08 eV, representing Al2O3 and Al (metal) bonds, respectively. In contrast, the used aluminum electrode after 1 and 10 cycles only shows Al2O3 peaks, indicating that the aluminum electrode is partially oxidized and the used electrode has undergone significant elemental changes. During the electrolysis process, the formed Al2O3 layer interacts with the local OH - Reaction, converted into AlO2 - , without affecting OH - Further evidence is provided by high-resolution O1s spectroscopy ( Figure 3 ) observed that the initial aluminum electrode showed double peaks at 531.98 eV and 533.38 eV, representing the CO and O-Al bonds in the relevant preparation process. In contrast, the aluminum electrode after use mainly contained O-Al bonds, except for the CO bonds, indicating that it was oxidized by OH during the electrolysis process. - Ion etching.

[0058] After SEM and AFM characterization, the present invention also carried out XRD analysis, and the results are shown in Figure 5 .

[0059] like Figure 5 As shown in Figure 2, the four significant peaks at 38.49°, 44.80°, 65.17° and 78.30° are characteristic XRD signals of Al, which are attributed to the (111), (200), (220) and (311) crystal planes, respectively. The disappearance of the (111) peak and the weakening of the (200), (220) and (311) crystal plane intensities provide evidence for the oxidation of the Al electrode by OH. - Additional evidence of corrosion, consistent with SEM, AFM and XPS characterization results.

[0060] In order to better characterize the electrochemical properties of the aluminum electrode, the present invention conducted electrochemical impedance spectroscopy (EIS) measurements after SEM and AFM characterization. The measurement results are shown in Figure 6 .

[0061] Figure 6 The results show that the original aluminum electrode exhibited the lowest charge transfer resistance (Rct, 114.3 ohms), which increased slightly to 118.0 ohms after 1 cycle and increased to 127.7 ohms after 10 cycles. This indicates that the charge transfer characteristics of the aluminum cathode are relatively stable as the electrolysis process proceeds, which is conducive to PFOA degradation cycle treatment under long-term operating conditions.

[0062] Fundamentally, the decomposition of organic pollutants by electrochemical reduction can be carried out through dissociative electron transfer (DET) at the cathode or indirectly through electrochemically generated reduction intermediates. Although the removal of PFOA is theoretically thermodynamically feasible at potentials below -1.2 V vsAg / AgCl, DET-mediated PFOA defluorination reactions have rarely been reported, initially due to the electrostatic repulsion between PFOA and the cathode in aqueous solution. For example, linear sweep voltammetry (LSV, Figure 7 As shown in (a), the applied cathode potentials were -1.7 V and -1.9 V vs Ag / AgCl, respectively, corresponding to current densities of 10 mA cm -2 and 25 mA cm -2 Despite the slight difference in cathode potential (0.2 V), the removal rate of PFOA was significantly different, i.e., 0.0039 min at -1.7 V. -1 , 0.0125min at -1.9V -1 From a thermodynamic point of view, it is unlikely that such a small difference in cathode potential would have a significant effect on the removal of PFOA.

[0063] Therefore, the present invention further compares the degradation of PFOA by titanium (Ti), a commonly used cathode material in electrochemical systems (current density 25 mA cm -2 ). The LSV curves of the original aluminum cathode and the Ti cathode are shown in Figure 7 Figure b shows that the potential of the Ti cathode is -2.8 V vs Ag / AgCl, which is 0.9 V higher than that of the aluminum cathode. The degradation rates of PFOA by the original aluminum cathode and the Ti cathode are shown in Figure 7 In Figure c, it can be seen that the degradation efficiency of the Ti cathode is 21.4%, which is much lower than the efficiency of the aluminum cathode (97.4%). Figure 7 The degradation rate constant of the corresponding fitting curve shown in (d) is 0.0010min -1 (Ti cathode) and 0.0125min -1 (Al cathode).

[0064] The large differences in degradation efficiency and rate between Al and Ti cathodes clearly indicate that the decomposition of PFOA is not dependent on DET cathode reduction.

[0065] In order to identify free radicals that may be involved in the degradation of PFOA, tert-butyl alcohol (TBA) was added as a H* scavenger and NO3 - As e aq - Then, ECL / CL measurements were performed, using luminol (LH2) as the luminescent agent under alkaline conditions to generate e aq -Provide direct evidence. Since luminol has a pKa1 of 6.7 and a pKa2 of 15.1, LH is mainly present in a single deprotonated form. - The chemiluminescent pathway of luminol usually begins with hydrogen atom abstraction (Equation 5) or rapid deprotonation of LH· free radicals formed by one-electron oxidation (Equation 6). ·- When used as an oxidant, LH- generates L ·- , then in a strong reducing agent e aq - When the rate of the protonation reaction (Equation 10) is faster than the deexcitation reaction (Equation 9), the emitting species is considered to be LH - *.

[0066] LH - +O2 ·- →L ·- +HO x (5)

[0067] LH - +O2 ·- →L ·- +H + +O x - (6)

[0068] e aq - +O2→O2 ·- (7)

[0069] L ·- +e aq - →L 2-* (8)

[0070] L 2-* →L 2- +hv (9)

[0071] L 2- +H2O→LH - +OH - (10)

[0072] pH(OH - concentration) is Al production e aq - In order to study the change of pH value of aluminum cathode, the present invention detects the OH near the aluminum cathode during electrolysis. - Due to the technical difficulty of measuring the local pH value experimentally, the local [OH - ] Theoretical calculations were performed. According to Faraday's law, assuming 100% Coulomb efficiency and no consumption of generated OH- , and uniformly mixed in the boundary layer, the theoretically maximum local [OH - ] can be calculated by Equations 11 and 12 relative to the boundary layer thickness (δ, m) and electrolysis time (t, s).

[0073]

[0074] Where It is the current (A), z is the number of electrons transferred in the reaction (z = 1), and F is the Faraday constant 96485 (C·mol -1 ), S is the cathode (S = 0.0012 m 2 ) area, δ is the boundary layer thickness (m).

[0075] Similar to PFOA, other fluorinated compounds are also known as refractory pollutants and pose a high risk to aquatic ecology. In order to evaluate the applicability of decomposing other fluorinated compounds, the present invention also studied the degradation of ofloxacin (OFX) and florfenicol (FLO) by the aluminum cathode ARP system.

[0076] In order to confirm that Al produces e aq - In order to play an important role in the degradation of PFOA, the present invention also studies the use of another typical amphoteric metal zinc (Zn) as the cathode to degrade PFOA.

[0077] The inhibition of H* scavenger on PFOA degradation at aluminum cathode is shown in Figure 8 .

[0078] ESR signals obtained using DMPO as a free radical scavenger (a), e aq - The inhibitory effect of scavengers on the degradation of PFOA by aluminum cathode system (b), the change of ECL signal of luminol as probe over time under different conditions (c) ([luminol] = 0.1 μM, pH = 11.0) and the theoretically calculated local pH value (d) are shown in Fig. 9 , Fig. 9 The inset in (d) is the measured cathodic solution [OH - ]value.

[0079] The degradation kinetic fitting curves of PFOA degradation by aluminum cathode ARP system under different NaNO3 concentrations are shown in Fig.10 .

[0080] In 10 consecutive experiments, the removal rate of PFOA in the aluminum cathode ARP system changes with time (a), the removal rate of OFX and FLO in the aluminum cathode ARP system (b), the degradation rate of PFOA in the aluminum and zinc cathode reduction system (c) and the defluorination rate of PFOA in the aluminum and zinc cathode reduction system (d) are shown in Fig.11 .

[0081] When different concentrations of TBA were added to the cathode solution to quench H*, the PFOA degradation rate decreased slightly with the increase of TBA concentration from 0 mM to 100 mM, which was about 10% ( Figure 8 As shown in the ESR data ( Fig. 9 In (a), the presence of H* was verified by observing nine characteristic peaks of DMPO-H adduct on the aluminum electrode. Figure 8 As a result, H* is unlikely to be the main reducing species responsible for PFOA degradation.

[0082] like Fig. 9 As shown in Figure c, no CL signal was observed in the blank group, which ruled out the spontaneous luminescence of luminol at pH = 11.0. No CL signal was observed in the titanium cathode benchmark group in alkaline aqueous solution. It is worth noting that a clear luminescence signal was detected on the aluminum cathode, which clearly proved that the e aq - The generation of aq - It is favorable for the CL of luminol in alkaline solution. In addition, at 25 mA cm -2 ECL measurements of the aluminum cathode were also performed at a current density of 2.3 s. It is evident that the ECL signal intensity increases sharply when the aluminum cathode is powered by electrolysis, followed by a sharp drop when the power is removed at 600 s. Together, the CL / ECL measurements provide a promising prospect for the generation of e-waste in the alkaline microenvironment adjacent to the aluminum cathode. aq - direct evidence of.

[0083] For the initial bulk PFOA solution, a pH of ~4.0 ( Fig. 9 d), then increased to ∼11.0 at 0.5 h of electrolysis, and then showed slight changes as the electrolysis proceeded, resulting in [OH - ]From 1×10 -10 Increased to 0.0013 mol L -1 (pH 4.0~11.0). Theoretical calculation results ( Fig. 9 Middle d) shows that local [OH - ] is negatively correlated with the thickness of the boundary layer on the Al cathode. When the maximum thickness of the boundary layer is assumed to be 1 mm, theoretically, after 30 min of electrolysis, lg[OH - ] is 0.7, and after 240 min of electrolysis, lg[OH - ] is 1.6, and the corresponding [OH - ] were up to 4.7 mol L -1 and 37.3 mol L -1 In fact, on the Al cathode where hydrogen evolution occurs during water electrolysis, if the boundary layer is thin, the local [OH- ] may be higher. That is, HER is the local OH - The enrichment of creates a suitable condition for it to react with Al to generate e aq - , which is the key reduction intermediate responsible for the local decomposition of PFOA.

[0084] like Fig.11 As shown in (a), after 10 consecutive cycle tests, the degradation rate of PFOA can be maintained at ~95%, indicating that the aluminum cathode ARP system has good reusability under long-term operation.

[0085] like Fig.11 As shown in (b), FLO and OFX were 100% degraded by the ARP system based on Al cathode when the electrolysis time was 0.5 and 3.0 h, respectively.

[0086] like Fig.11 As shown in Figures c and d, with Zn as the cathode, the degradation rate of PFOA was 36.5% after 4 hours of electrolysis, and the defluorination efficiency of PFOA was only 42.8% after 12 hours of electrolysis. These values ​​are much lower than those of Al cathode, which can be well explained by the interaction between Al and Zn and OH - This further provides the basis for the e- aq - Degradation of PFOA provides evidence.

[0087] Based on Al cathode system, the electrogeneration of hydrated electrons aq - Schematic diagram of the PFOA degradation mechanism is shown in Fig.12 .

[0088] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for electrogenerating hydrated electrons using an amphoteric metal cathode, characterized in that: The following steps are involved: A diaphragm electrolyzer is constructed using amphoteric metals as cathode materials, and hydrated electrons can be generated in the cathode chamber when electricity is applied.

2. The method for electrogenerating hydrated electrons using an amphoteric metal cathode according to claim 1, characterized in that: The amphoteric metal is aluminum.

3. Use of the method for electrogenerating hydrated electrons using an amphoteric metal cathode as described in claim 1 or 2 in the degradation of perfluorooctanoic acid.

4. Use of the method for electrogenerating hydrated electrons using an amphoteric metal cathode as described in claim 1 or 2 in the degradation of fluorine-containing organic matter.

5. A method for degradation of perfluorooctanoic acid mediated by electrogenerated hydrated electrons using an amphoteric metal cathode, characterized in that: The following steps are involved: A diaphragm electrolytic cell is constructed using amphoteric metal as the cathode material and an electrolyte containing at least perfluorooctanoic acid as the cathode chamber electrolyte, and the degradation of perfluorooctanoic acid can be achieved by turning on power.

6. The method for degradation of perfluorooctanoic acid mediated by electrogenerated hydrated electrons using an amphoteric metal cathode according to claim 5, characterized in that: The amphoteric metal is aluminum.

7. A method for degradation of fluorinated organic matter mediated by electrogenerated hydrated electrons using an amphoteric metal cathode, characterized in that: The following steps are involved: Amphoteric metals are used as cathode materials, and an electrolyte containing at least fluorinated organic matter is used as the cathode chamber electrolyte to construct a diaphragm electrolytic cell, and the degradation of fluorinated organic matter can be achieved by powering on.

8. The method for degradation of fluorinated organic matter mediated by electrogenerated hydrated electrons using an amphoteric metal cathode according to claim 7, characterized in that: The amphoteric metal is aluminum.

Citation Information

Patent Citations

  • Application of MOS (Metal Oxide Semiconductor) electrochemical cathode to electrically producing hydrated electrons to remove perfluorinated compounds

    CN114715978A

  • Method and device for treating PFASs wastewater through cooperation of zinc-based electric flocculation and electrocatalytic oxidation

    CN114873694A

  • Electric flocculation device and method for removing fluorine ions in perfluorinated compound degradation wastewater and application of electric flocculation device and method

    CN115259301A

  • Water treatment apparatus

    JP2003311274A

  • Gamma ray electricity generating method

    JP2018100866A